1996
DOI: 10.1002/pc.10639
|View full text |Cite
|
Sign up to set email alerts
|

Braided thermoplastic composites from powder‐coated towpregs. Part I: Towpreg characterization

Abstract: Textile preforms offer the potential for producing low cost, complex shaped, advanced composite structures. For thermoplastic composites in particular, it is advantageous to incorporate the resin in the tow prior to textile processing since it is difficult to impregnate dry fabrics with thermoplastic melts. Incorporating resin in the tows tends to alter the properties of the tows that are critical for textile processibility. In this paper, carbon fiber tows coated with nylon powder are studied. They are charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 7 publications
0
17
0
Order By: Relevance
“…Summarizing all the results, they concluded that the air-textured commingled yarns with optimized fiber sizing provide the highest transverse modulus and strength, as well as the higher crack resistance [8]. Ramasamy et al [10,11] have studied braided thermoplastic composites from carbon fiber/polyamide 6 powder-coated yarns and also the influence of the consolidation conditions on the laminate properties. The impregnation of fabric structures with thermoplastic polyamide 6.6 in continuous manufacturing was accomplished along the direction of thickness rather than in-plane as usual in liquid composite manufacturing techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Summarizing all the results, they concluded that the air-textured commingled yarns with optimized fiber sizing provide the highest transverse modulus and strength, as well as the higher crack resistance [8]. Ramasamy et al [10,11] have studied braided thermoplastic composites from carbon fiber/polyamide 6 powder-coated yarns and also the influence of the consolidation conditions on the laminate properties. The impregnation of fabric structures with thermoplastic polyamide 6.6 in continuous manufacturing was accomplished along the direction of thickness rather than in-plane as usual in liquid composite manufacturing techniques.…”
Section: Introductionmentioning
confidence: 99%
“…[12]. Among the available hybrid yarns, commingled thermoplastic yarns are more suitable for braiding because of their easy handleability [13,14] and relatively superior drapeability. Previous literature shows several instances of incorporation of commingled thermoplastic yarns in a braiding process [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…In terms of use as a polymer matrix in fibre-reinforced composite materials, one concept that was previously explored in the aerospace industry was the production of 'towpreg', where carbon-fibre tows were individually spread and either thermoset or thermoplastic powder was sprayed into the tow. These tows could subsequently be braided, woven, turned into tape for automated tape placement, or used to make pultruded sections [17][18][19]. By depositing the powder directly into the tow, the polymer was not required to flow into the tows, making the process suitable for use with thermoplastic powders.…”
Section: Introductionmentioning
confidence: 99%